2021
DOI: 10.21203/rs.3.rs-295872/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CLEC10A is a Potential Prognostic Biomarker and Immune Regulator of Tumor Microenvironment in Breast Cancer

Abstract: The communication between tumor cells and immune cells influences the ecology of the tumor microenvironment in breast cancer, as well as the disease progression and clinical outcome. The aim of this study was to investigate the prognostic value of the immunomodulatory factor CLEC10A in breast cancer. We applied the CIBERSORT and ESTIMATE calculation methods to calculate the proportion of tumor-infiltrating immune cells (TICs) and the amount of immune and stromal components in 1053 BRCA cases from The Cancer Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…[35][36][37] Additionally, recent research on breast cancer led to the discovery that CLEC10A binds to GalNAc residues found in breast cancer tissue. 38,39 Therefore, it seems obvious that incorporating sugars in nucleic acid vectors would be advantageous for delivery for the treatment of specific cancer types.…”
Section: Paper Polymer Chemistrymentioning
confidence: 99%
“…[35][36][37] Additionally, recent research on breast cancer led to the discovery that CLEC10A binds to GalNAc residues found in breast cancer tissue. 38,39 Therefore, it seems obvious that incorporating sugars in nucleic acid vectors would be advantageous for delivery for the treatment of specific cancer types.…”
Section: Paper Polymer Chemistrymentioning
confidence: 99%